False Re-Representations in Self-Knowledge - Pacholik-Żuromska, Anita (Logic and Logical Philosophy, 2020)
Self-knowledge (SK) is a natural ability of the human cognitive system and is defined as a complex re-representation of knowledge subject has about her own internal states. It is composed of two basic representations: the representation of I and the representation of the experienced state. SK has a propositional (i.e. language-like) form and can be expressed in the form of self-reports like “I believe that I believe that p”. It has then the form of a second-order belief which, as a re-representation, generates the following problem concerning false representations: if the first-order representations of the I or of experienced states can be false like in cases of self-illusions or disorders like somatoparaphrenia, then how can error in self-cognition inherited by the re-representation (i.e. by SK) be avoided? I claim that the re-representational model of SK is a useful but artificial tool for the description of the components of SK; however, it is misleading to think of it as capturing the truth about SK. I propose here a representational model of SK which reduces those beliefs constituting SK to first-order beliefs which are sufficient as constituents of SK.